Defining Trust Markers - Butler, Blaine (Information services & use, 2025)
This paper is a visual summary of the key issues raised during a panel session entitled “Towards Standards for Trust Markers on Published Content” that was part of the 2024 NISO Plus Global virtual Conference held September 17–18, 2024. The author discusses paper mills and the efforts spearheaded by United2Act and the Committee on Publication Ethics (COPE) to mitigate the unethical behavior of paper mills that are seriously eroding research integrity and public trust in science.